this Pendekatan Pembelajaran Deep Learning Sebagai Paradigma Baru dalam Implementasi Kurikulum Merdeka - mohammad mohan; Endah Rahmawati; M. Yunus Abu Bakar (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study explores the relevance of deep learning as an instructional approach within the implementation of the Independent Curriculum, using a qualitative literature review methodology. Findings indicate strong alignment between deep learning and the curriculum’s core principles particularly its emphasis on meaningful understanding, critical thinking, conceptual integration, and reflective engagement. Instructional models such as project-based, inquiry-based, and problem-based learning emerge as effective enablers of deep learning. Nevertheless, key challenges remain, including varying levels of teacher preparedness, insufficient infrastructure, and ethical considerations surrounding digital technology use. The study thus underscores the need for sustained teacher professional development, equitable access to learning resources, and responsible, ethically grounded integration of educational technology. Overall, deep learning offers a robust and actionable framework for advancing the transformative goals of the Independent Curriculum.